2006
DOI: 10.3201/eid1206.050245
|View full text |Cite
|
Sign up to set email alerts
|

Co-infections of Adenovirus Species in Previously Vaccinated Patients

Abstract: Adenoviral infections associated with respiratory illness in military trainees involve multiple co-infecting species and serotypes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
38
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 38 publications
(40 citation statements)
references
References 40 publications
2
38
0
Order By: Relevance
“…Thus, as was seen in the results of other studies, infections with multiple ADV types are not unusual (2,5,6,7,9,11,13,14).…”
Section: Adenovirus (Adv) Infections Are Common In Childhoodsupporting
confidence: 83%
“…Thus, as was seen in the results of other studies, infections with multiple ADV types are not unusual (2,5,6,7,9,11,13,14).…”
Section: Adenovirus (Adv) Infections Are Common In Childhoodsupporting
confidence: 83%
“…As shown by others (33,34,35), species-and type-specific PCR assays are capable of revealing coinfections with different HAdVs that otherwise might go undetected. In this study, we identified several specimens by our qPCR assays that contained two HAdV types, one predominant type and one subordinate type.…”
Section: Discussionmentioning
confidence: 88%
“…It is important to note that such a preliminary study should be confirmed eventually with a whole-genome determination for a thorough description, since possible recombination events would not be surveyed. Genome recombination requires coinfection, which is observed in HAdV infections (8,26,39). Putative recombinants, based on the neutralization epsilon and hemagglutination gamma determinants, are recognized as different prototypes by the community, with additional field strains described based on these two markers (SN and hemagglutination inhibition assays) as case studies in the literature (9,11,12).…”
Section: Discussionmentioning
confidence: 99%